Response of Growth Citronellal Grass (Cymbopogon nardus L) by Acaulospora sp Mycorrizha and Different Water Treatments in Ultisol - Netti Herawati (JERAMI : Indonesian Journal of Crop Science, 2022)
Citronella grass (Cymbopogon nardus L) is one of the essential oil-producing plants from the Gramineae group. This research was conducted in the Greenhouse of the Faculty of Agriculture, Andalas University, Padang from August 2017 until January 2018. This study aimed to determine the effect of Acaulospora sp and different water treatments on the growth of citronella grass in ultisol. A completely randomized design with two factors was used. The first factor was treatment with or without Acaulospora sp. The second factor was the water supply which consisted of three treatments (saturated, three quarters saturated and half saturated soil). Every treatment was repeated three times. Data were analyzed by analysis of variance using the F-test at the 5% level. Significant differences were further tested using Duncan’s New Multiple Range Test also at the 5% level. Treatment with Acaulospora sp and 75% saturated soil gave the best number of leaves and canopy to root ratio. Treatment with Acaulospora sp showed the best results for the number of tillers, stem diameter, root dry weight, and dry weight of the citronella plants. Acaulospora spp promote the growth of citronella grass.